Efektivitas Program In House Training (IHT) dalam Meningkatkan Mutu Pembelajaran Mendalam (Deep Learning) di SMA Muhammadiyah Galela - Adam, Adiyana; Sebe, Kamarun M.; Eku, Amran; Silawane, Nurjannah; Umagap, Wirda (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to describe the effectiveness of the In House Training (IHT) program in improving the quality of deep learning-based instruction at SMA Muhammadiyah Galela. The research employed a qualitative descriptive approach, involving 23 teachers from various subject areas as participants. Data were collected through interviews, observations, and documentation, then analyzed using an interactive model of data reduction, display, and conclusion drawing. The results show that all participants successfully designed teaching modules aligned with the 2025 learning outcomes and the Merdeka Curriculum by integrating deep learning principles with Artificial Intelligence (AI). The training process, which included theoretical sessions, practical activities, and evaluation through module presentations, was effective in enhancing teachers’ competence, creativity, and collaboration. This study concludes that IHT is an adaptive and sustainable strategy to strengthen teacher professionalism and improve deep learning practices in secondary schools..